Sistem Informasi Geografis Pemetaan Sungai dan Bangunan Utama pada Daerah Irigasi Kewenangan Provinsi di Pulau Timor - Christiani Chandra Manubulu; Frederikus D. Ndouk (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Water is one of the basic human needs for various daily needs. One source of water that is often used by the general public is river water. With proper utilization, river water can support the economic development of the surrounding community. The main priority for water use is for domestic use such as drinking water and household needs and also used for industrial, agricultural, plantation, livestock, fishery, and so on. Optimal use of rivers for irrigation areas must be supported by information related to river conditions and buildings in rivers. Therefore it is necessary to make a database related to river conditions and irrigation building conditions. One of the software used in making a river database in the Provincial Irrigation Authority on Timor Island is Quantum Geographic Information System (QGIS) because it is open-source software that does not require a license but provides ample room for users to add functions such as software other paid mapping.